Association Between Nutritional Status and Gross Motor Skills Development in Children Aged 1-3 Years at Posyandu in Situ Udik Health Center Area - Triswanti Triswanti; Nurul Herawati; Intan Sari Mawar Indah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Gross motor development in children aged 1–3 years is a crucial aspect of growth and development, influenced by various factors, one of which is nutritional status. Good nutritional status plays a role in optimizing children's growth and development, including gross motor skills. This study aims to analyze the relationship between nutritional status and gross motor development in children aged 1–3 years at the Posyandu within the working area of Situ Udik Community Health Center (Puskesmas). This study employs a quantitative design with a cross-sectional approach. The research sample consists of children aged 1–3 years selected using a random sampling technique. Nutritional status was measured using an anthropometric approach, specifically weight-for-age (W/A), while gross motor development was assessed using the validated Denver Development Screening Test (DDST II) observation sheet. Data analysis was conducted using the chi-square statistical test to determine the relationship between nutritional status and gross motor development. The results indicate a significant relationship between nutritional status and gross motor development in children aged 1–3 years (0.013, p ≤ 0.05). Children with good nutritional status tend to have optimal gross motor development compared to those with undernutrition or overnutrition. These findings suggest that good nutritional status is a supporting factor in early childhood gross motor development. Therefore, regular monitoring of nutritional status and parental nutrition education are essential steps in supporting children's optimal growth and development.